STRATEGI PROMOSI DESTINASI WISATA PANTAI BUNTU MATABING PADA DINAS KEBUDAYAAN DAN PARIWISATA MELALUI MEDIA SOSIAL DALAM MENINGKATKAN KUNJUNGAN WISATAWAN DI KABUPATEN LUWU - Ratnafitasary , Ratnafitasary; Ahdan, Ahdan; Muttaqin Mustari , Andi (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
This study aims to examine the Promotion Strategy of the Culture and Tourism Office of Luwu Regency in increasing tourist visits to the Buntu Matabing Beach destination, and to determine the effectiveness of tourism promotion through social media at the Buntu Matabing Beach tourist destination. The results of this study indicate that the tourism promotion strategy has been running well, although not yet fully optimal, tourism development at Buntu Matabing Beach is supported by related service programs in the form of Strategic Plans (Renstra) and Work Plans (Renja) in promoting tourism, tourism development on the coast. Buntu Matabing turns out to have several obstacles, including: tourism objects have not been well organized and managed, budget allocations from local governments are still limited, and there is no special section that handles tourism promotion issues, for example the Publication Division, related agencies and stakeholders in the world of tourism. took various ways to overcome various obstacles encountered, including: optimizing existing resources and establishing cooperation with other parties/agencies/institutions to develop Buntu Matabing Beach tourism in Luwu Regency.